Room temperature synthesized solid solution AuFe nanoparticles and their transformation into Au/Fe Janus nanocrystals. Issue 23 (7th June 2021) - Efremova, Maria V.; Spasova, Marina; Heidelmann, Markus; Grebennikov, Ivan S.; Li, Zi-An; Garanina, Anastasiia S.; Tcareva, Iana O.; Savchenko, Alexander G.; Farle, Michael; Klyachko, Natalia L.; Majouga, Alexander G.; Wiedwald, Ulf
Abstract : Solid solution AuFe nanoparticles with paramagnetic Fe atoms in the Au matrix synthesized at 25 °C transform into Janus particles upon annealing at 700 °C with the ferromagnetic bcc Fe phase epitaxially grown on fcc Au. Abstract : Solid solution AuFe nanoparticles were synthesized for the first time under ambient conditions by an adapted method previously established for the Fe3 O4 –Au core–shell morphology. These AuFe particles preserved the fcc structure of Au incorporated with paramagnetic Fe atoms. The metastable AuFe can be segregated by transformation into Janus Au/Fe particles with bcc Fe and fcc Au upon annealing. The ferromagnetic Fe was epitaxially grown on low index fcc Au planes. This preparation route delivers new perspective materials for magnetoplasmonics and biomedical applications and suggests the reconsideration of existing protocols for magnetite–gold core–shell synthesis.